OLFACTOR CODE AS AN OBJECT OF LINGUISTIC RESEARCH - Burkhanova Mashxuraxon Muhammadovna (Scholar Express Journal, 2023)
This article presents the scientific-theoretical views that the sense of smell can be studied as one of the methods of perception, and that it can be an object of research for natural and humanitarian sciences. The study of smell as part of non-verbal communication and its communicative importance are discussed
Keywords: Perception; smell; communication; sign